Psychometric Evaluation of MFI-20 and OFER-15 Instruments for Measuring Occupational Fatigue Among Nickel Miners - Muhammad Rafsanjani; Adithya Sudiarno (Green Publisher Indonesia, 2025)
Occupational fatigue is a multidimensional construct that affects physical, mental, and emotional functioning, especially in high-risk sectors such as mining. This study aims to evaluate the psychometric properties of two widely used instruments—Multidimensional Fatigue Inventory (MFI-20) and Occupational Fatigue Exhaustion Recovery (OFER-15)—in measuring fatigue among nickel mine workers in Indonesia. A total of 358 respondents completed the instruments as part of a broader fatigue risk assessment. Internal consistency was examined using Cronbach’s Alpha, while convergent and discriminant validity were assessed through correlation analysis among dimensions. Results showed high reliability for both instruments (α > 0.70 across all subscales). Most items demonstrated significant convergent validity (r > 0.4, p < 0.05), and inter-dimensional correlations supported discriminant validity (r < 0.7). These findings suggest that MFI-20 and OFER-15 are valid and reliable tools for assessing occupational fatigue in mining contexts. The study supports the use of both instruments for fatigue monitoring and intervention planning in industrial settings.